Interfacial structure of upward gas–liquid annular flow in inclined pipes. (November 2020) - Fershtman, Adam; Robers, Lukas; Prasser, Horst-Michael; Barnea, Dvora; Shemer, Lev
Highlights: A novel three-dimensional multilayer conductance sensor is applied to investigate the wavy interfacial structure in gas-liquid annular flow. The sensor allows obtaining 3D temporally and spatially resolved data. Detailed statistical analysis is carried out to determine the principal wave parameters for different gas and liquid flow rates and pipe inclination angles. The dependence of the interfacial wave characteristics on the azimuthal location within the pipe is studied as well. Abstract: Temporal and spatial-resolved data on the interfacial structure in upward vertical and inclined two-phase annular flows were accumulated using a novel non-intrusive multilayer conductance sensor. The sensor provides simultaneous measurement of the film thickness across the entire pipe circumference, enabling a three dimensional reconstruction of the wavy interface. Measurements were performed for two liquid (water) flow rates and a single high gas (air) flow rate. Three types of interfacial waves were identified, including ripples, disturbance and rogue waves. Rogue waves can be described as an infrequent solitary disturbance wave propagating over a ripple-dominant interface. Detailed statistical properties of the interfacial shape, such as the mean film thickness, wave height distribution, wave frequency spectra, wave propagation velocities and more, were obtained as a function the pipe inclination and azimuthal angle. The statistical analysis of the wavy interface presented in this study sheds light on a complex flow pattern of annular flow in inclined pipes, which has remained relatively unstudied experimentally. For inclined pipes, gravity imposes an asymmetric film distribution resulting in the thickest film at the bottom of the pipe. At this location, waves attain larger amplitudes while maintaining slower propagation velocities as compared to smaller amplitude waves at the top of the pipe. Generally, the wave frequency throughout the pipe circumference increases with inclination angle. For a larger liquid flow rate, the interface was found to be primarily dominant by disturbance waves. For a lower liquid velocity, the interfacial structure was found to be highly dependent on both the azimuthal and the inclination angles. An interface wave type map is presented as a function of those angles.